Mapping of the Tacaribe Arenavirus Z-Protein Binding Sites on the L Protein Identified both Amino Acids within the Putative Polymerase Domain and a Region at the N Terminus of L That Are Critically Involved in Binding - Wilda, Maximiliano (2008)
Tacaribe virus (TacV) is the prototype of the New World group of arenaviruses. The TacV genome encodes four proteins: the nucleoprotein (N), the glycoprotein precursor, the polymerase (L), and a RING finger protein (Z). Using a reverse genetics system, we demonstrated that TacV N and L are sufficient to drive transcription and replication mediated by TacV-like RNAs and that Z is a powerful inhibitor of these processes (Lopez et al., J. Virol. 65:12241-12251, 2001). More recently, we provided the first evidence of an interaction between Z and L and showed that Z's inhibitory activity was dependent on its ability to bind to L (Jácamo et al., J. Virol. 77:10383-10393, 2003). In the present study, we mapped the TacV Z-binding sites on the 2,210-amino-acid L polymerase. To that end, we performed deletion analysis and point mutations of L and studied the Z-L interaction by coimmunoprecipitation with specific sera. We found that the C-terminal region of L was not essential for the interaction and identified two noncontiguous regions that were critical for binding: one at the N-terminus of L between residues 156 and 292 and a second one in the polymerase domain (domain III). The importance of domain III in binding was revealed by substitutions in D1188 and H1189 within motif A and in each residue of the conserved SDD sequence (residues 1328, 1329, and 1330) within motif C. Our results showed that of the substituted residues, only H1189 and D1329 appeared to be critically involved in binding Z.